Lack of chemokine signaling through CXCR5 causes increased mortality, ventricular dilatation and deranged matrix during cardiac pressure overload. - Anne Waehre; Bente Halvorsen; Arne Yndestad; Cathrine Husberg; Ivar Sjaastad; Ståle Nygård; Christen P Dahl; M Shakil Ahmed; Alexandra V Finsen; Henrik Reims; William E Louch; Denise Hilfiker-Kleiner; et al. (PLoS ONE, 2011)
RATIONALE: Inflammatory mechanisms have been suggested to play a role in the development of heart failure (HF), but a role for chemokines is largely unknown. Based on their role in inflammation and matrix remodeling in other tissues, we hypothesized that CXCL13 and CXCR5 could be involved in cardiac remodeling during HF. OBJECTIVE: We sought to analyze the role of the chemokine CXCL13 and its receptor CXCR5 in cardiac pathophysiology leading to HF. METHODS AND RESULTS: Mice harboring a systemic knockout of the CXCR5 (CXCR5(-/-)) displayed increased mortality during a follow-up of 80 days after aortic banding (AB). Following three weeks of AB, CXCR5(-/-) developed significant left ventricular (LV) dilatation compared to wild type (WT) mice. Microarray analysis revealed altered expression of several small leucine-rich proteoglycans (SLRPs) that bind to collagen and modulate fibril assembly. Protein levels of fibromodulin, decorin and lumican (all SLRPs) were significantly reduced in AB CXCR5(-/-) compared to AB WT mice. Electron microscopy revealed loosely packed extracellular matrix with individual collagen fibers and small networks of proteoglycans in AB CXCR5(-/-) mice. Addition of CXCL13 to cultured cardiac fibroblasts enhanced the expression of SLRPs. In patients with HF, we observed increased myocardial levels of CXCR5 and SLRPs, which was reversed following LV assist device treatment. CONCLUSIONS: Lack of CXCR5 leads to LV dilatation and increased mortality during pressure overload, possibly via lack of an increase in SLRPs. This study demonstrates a critical role of the chemokine CXCL13 and CXCR5 in survival and maintaining of cardiac structure upon pressure overload, by regulating proteoglycans essential for correct collagen assembly.